Medulloblastoma harbor somatic mitochondrial DNA mutations in the D-loop region - Lüth, Maria; Deimling, Andreas von; Pietsch, Torsten; Wong, Lee-Jun; Kurtz, Andreas; Henze, Guenter; Driever, Pablo Hernáiz (Journal of pediatric hematology - oncology, 2010)
Despite the growing knowledge on molecular risk factors of the most common malignant brain tumor in childhood, medulloblastoma, its biology remains only partially understood. A previous study investigating the entire mitochondrial genome of medulloblastoma revealed a number of somatic mutations in tumor and corresponding cerebrospinal fluid samples. In our present study we sought to corroborate these results on somatic and germ line mutations by comparing the complete mitochondrial genome sequences of medulloblastoma tissue in a further cohort of patients. Analysis of the entire mitochondrial genome by temporal temperature gel electrophoresis and direct sequencing revealed 6 somatic mutations in 6 of 15 medulloblastoma. All changes were insertions, deletions, or substitutions restricted to the np 303 to 315 poly-C tract of the D-loop region. Three were changes from heteroplasmy to homoplasmy. Two were changes from heteroplasmy to heteroplasmy and one mutation represented a change from homoplasmy to heteroplasmy. In addition, 25 distinct germ line variations were identified. These results are in support of our previous findings on frequency of somatic mitochondrial mutations in medulloblastoma. Somatic alterations were found only in the hypervariable D-loop region, supporting the idea that these control regions contain hot spots for both, germ line variations and somatic alterations of the mitochondrial genome.
Gesehen am 19.04.2023